FORMING A PROFESSIONAL OUTLOOK IN THE FIELD OF PHYSICAL CULTURE AND SPORTS - K. Arov; O. Borisov; K. Marinchenko; G. Lundina; A. Kudrya (Вестник Северо-Кавказского федерального университета)
The article is devoted to the study of the development of physical culture and sports in Russia. Today, the formation of a professional worldview in the field ofphysical culture and sports is an important component of the state, social and economic policy of the state. In the current program of development of physical culture and sport noted that one of the main functions ofphysical culture and sport is to contribute to the formation ofa professional Outlook in the field of healthy lifestyles, as well as in the education of youth and the younger generation. The priority direction of our state's policy is primarily aimed at improving the health of the nation through the promotion of mass physical culture classes.